salivary biomarkers: future clinical investigation technique (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
Human saliva is a clear, slightly acidic biological fluid containing a mixture of secretions from multiple salivary glands, including the parotid, sublingual gland other minor glands beneath the oral mucosa as well as gingival crevice fluid.  Salivary diagnostics has evolved into a sophisticated science and serves as a subset of the larger field of molecular diagnostics, now recognized as a central player in a wide variety of biomedical basic and clinical areas.  Saliva biomarkers are source of indicators for local, systemic, and infectious disorders. The saliva based microbial, immunologic, and molecular biomarkers offers unique opportunities to bypass the painful invasive procedures such as biopsies and repeated blood draws by utilizing oral fluids to evaluate the condition of diseased individuals. Accurate and reliable early stage disease detection is the benefit of salivary biomarkers. Salivary biomarkers represent a promising non-invasive approach for oral cancer detection also. This review explains about the salivary biomarkers and their diagnostic approaches